Commercialization of innovative technologies : bringing good ideas to the marketplace - Touhill, C. J., 1938-; Touhill, Gregory J.; O'Riordan, Thomas A.; American Institute of Chemical Engineers (Hoboken, N.J. : John Wiley & Sons : AlChE, 2008)
This book covers new technology ideas and guides you through the complete lifecycle of product innovation, including screening, funding, development, and commercialization.
Establishing perspective -- Our perspective -- Developing an endgame -- Finding ideas -- Investing in ideas -- Assessing ideas -- Paying for and controlling ideas -- Developing ideas -- Designing and building technology -- Demonstrating technology -- Standardizing technology -- Packaging technology -- Applying technology -- Marketing and selling technology -- Tracking technology -- Monitoring technology -- Improving technology -- Building on success and learning from failure.
Includes bibliographical references (pages 239-240) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Technological innovations; Innovations; BUSINESS & ECONOMICS -- Structural Adjustment; Technological innovations; Kommerzialisierung; Projekt; Realisierung; Technische Innovation; Vermarktung